2013
DOI: 10.1371/journal.pone.0073253
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetics of Lactobacillus sakei Reveals Three Lineages with Distinct Evolutionary Histories

Abstract: Lactobacillus sakei plays a major role in meat fermentation and in the preservation of fresh meat. The large diversity of L. sakei strains represents a valuable and exploitable asset in the development of a variety of industrial applications; however, an efficient method to identify and classify these strains has yet to be developed. In this study, we used multilocus sequence typing (MLST) to analyze the polymorphism and allelic distribution of eight loci within an L. sakei population of 232 strains collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 56 publications
4
43
0
Order By: Relevance
“…A similar population structure was found for the wine-associated species Oenococcus oeni (31). Conversely, recombination both within and between subpopulations was common for Lactobacillus sakei (30).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…A similar population structure was found for the wine-associated species Oenococcus oeni (31). Conversely, recombination both within and between subpopulations was common for Lactobacillus sakei (30).…”
Section: Discussionsupporting
confidence: 68%
“…Previous studies on the population genetics of food-associated bacterial species have shown that division into subpopulations reflects adaptations to different niches rather than geographical isolation (30,31). The strains in this study were from food products manufactured at 22 production plants located across Finland.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the genome of L. sanfranciscensis enables it to grow easily in this environment and contributes to its ability to out-compete other bacteria in traditional sourdough (Vogel et al, 2011). Unlike L. sanfranciscensis, the other LAB species detected in this study, L pentosus, L. sakei, L. plantarum and L. kimchii, have already been detected in sourdough and are also frequently isolated from other habitats (Botta and Cocolin, 2012;Chaillou et al, 2013;Corsetti and Gobbetti, 2002;Yoon et al, 2000).…”
Section: Discussionmentioning
confidence: 76%
“…The dissociation index was calculated with Start2 (32). Recombination analysis and phylogenetic tree inference under the neutral coalescent model were performed with ClonalFrame as previously described (37).…”
Section: Methodsmentioning
confidence: 99%